Renewing core values to drive strategy execution : Action research on a Finnish MNE and its stakeholders - Ala-Härkönen, Antti (My University, 2025)
The renewal of core values is an important strategic process for multinational enterprises (MNEs). The targeted impact of the process is that core values would shape the company’s employees’ daily behaviour, decision making and ways of working, thus also forming the basis for the company’s corporate culture and more efficient strategy execution. The definition of core values and corporate-level strategy development are process-wise closely linked with each other. This thesis examines how the renewal of core values can drive strategy execution in multinational enterprises by exploring the connection between the renewal of core values and strategy execution. Action research was conducted in a Finnish energy-sector MNE that recently went through a core value renewal process in 2024–2025. The research combines a literature review on the importance of core value definition as part of strategy together with qualitative data from the case including eight semi-structured interviews, document analysis on meeting notes and post-launch workshop observations. The study finds that multinational enterprises should consider renewing their core values when strategic, internal or external changes create a clear organisational need for the strengthening of strategy execution. In the case firm studied, both market shifts and internal restructuring acted as catalysts for a need to renew core values and to align the existing strategy with the new core values. The introduction of three renewed core values simplified the previous set of complex guiding principles, involved and energised employees, and also signalled to the whole organisation the beginning of a new strategic era. An intentionally inside-out implementation approach strengthened internal buy-in of the renewed core values before external communication, thus laying the foundation for improved stakeholder trust and engagement. The renewed core values also created a clearer visionary line between everyday decision-making and longer-term strategic objectives, thus importantly enhancing strategy execution. This thesis contributes to international business and strategy development literature by bridging the importance of value-based organisational change with strategy execution. The renewal of core values is seen as an important and integral phase in the process of efficiently executing the company’s strategy and in strengthening the company’s competitive advantage. The action research design provides novel empirical insights into the topic and the findings provide practical guidance for managers on how to renew core values in a way that reinforces the company’s strategy execution, the achievement of strategic targets and stakeholder relationships.

Ydinarvojen uudistaminen on tärkeä strateginen prosessi monikansallisille yrityksille. Prosessin tavoiteltu vaikutus on, että ydinarvojen määrittely ohjaisi yhtiön työntekijöiden päivittäistä käyttäytymistä, päätöksentekoa ja työskentelytapoja, luoden samalla perustan yhtiön yrityskulttuurille ja strategian tehokkaammalle toteutukselle. Ydinarvojen määrittely ja yritystason strategianmuodostus ovat prosessimielessä tiiviisti yhteydessä toisiinsa. Tämä tutkimus tarkastelee, miten ydinarvojen uudistaminen voi parantaa strategian toteuttamista monikansallisissa yrityksissä analysoimalla ydinarvojen uudistamisen ja strategian toteuttamisen välistä yhteyttä. Tutkimus toteutettiin toimintatutkimuksena suomalaisesta energiasektorin monikansallisesta yrityksestä, joka uudisti ydinarvonsa vuosina 2024–2025. Tutkimus yhdistää kirjalliskatsauksen ydinarvojen laatimisen tärkeydestä osana strategiaa sekä case-yrityksestä kerätyn laadullisen aineiston, johon sisältyy kahdeksan puolistrukturoitua haastattelua, projektimuistiinpanoja sekä työpajahavaintoja arvojen lanseerauksen jälkeisestä koulutuspäivästä. Tutkimuksen tulokset osoittavat, että monikansallisten yritysten tulisi harkita ydinarvojensa uudistamista silloin, kun strategiset, sisäiset tai ulkoiset muutokset luovat selkeän tarpeen organisaation strategian toteuttamisen vahvistamiselle. Tutkitussa case-yrityksessä markkinamuutokset ja sisäiset uudelleenjärjestelyt toimivat katalyyttinä tarpeelle uudistaa ydinarvot sekä yhtenäistää strategian toteutus yhdessä uusien ydinarvojen kanssa. Kolmen uudistetun ydinarvon käyttöönotto selkeytti aiempaa monimutkaista johtamisperiaatteiden kenttää, osallisti ja energisoi työntekijöitä sekä viesti koko organisaatiolle uuden strategisen aikakauden alkamisesta. Tietoisesti ”inside-out”-periaatteella toteutettu arvojenuudistusprosessi vahvisti työntekijöiden sisäistä sitoutumista ennen ulkoista viestintää, ja loi siten perustan parantuneelle sidosryhmäluottamukselle ja -sitoutumiselle. Uudistetut ydinarvot loivat myös selkeämmän visionaarisen linjan päivittäisen päätöksenteon ja pidemmän aikavälin strategisten tavoitteiden välille, mikä tärkeällä tavalla vahvisti strategian toimeenpanoa. Tutkimus täydentää kansainvälisen liiketoiminnan ja strategianmuodostuksen kirjallisuutta yhdistämällä arvoperusteisen organisaatiomuutoksen ja strategian toteuttamisen näkökulmat. Ydinarvojen uudistaminen nähdään tärkeänä ja integroituna vaiheena prosessissa, joka tähtää yhtiön strategian tehokkaaseen toimeenpanoon ja kilpailuedun vahvistamiseen. Toimintatutkimusasetelma tuottaa uusia empiirisiä havaintoja tutkittuun aiheeseen, ja tulokset tarjoavat käytännön ohjeita johtajille ydinarvojen uudistamiseen tavalla, joka vahvistaa yhtiön strategian toteuttamista, strategisten tavoitteiden saavuttamista sekä sidosryhmäsuhteita.
Keywords: Core values, value renewal, strategy execution, strategic alignment, stakeholders, organisational culture, multinational enterprise (MNE), action research